Equality and Social Inclusion: Educational Challenges for Today's Schools - Rosa Blanco (Universidad Autónoma de Madrid, 2018)
The educational process has not been able to overcome social discrepancies any more than it has been able to reduce the gap between classes; this is why mayor efforts must be made to transform education into a catalyst for social equality. The social involvement movement has fought restrictive and discriminative environments in educational systems for years. This has demanded a constant growth towards a diverse and unique system capable of catering to collective and individual needs; providing the same level of quality and learning to the whole of the population. In order to do this, a separation must be considered between education for everyone, and education for those deemed "different".